GEOGRAPHICAL ELEMENTS IN NEŞET ERTAŞ FOLK SONGS IN THE CONTEXT OF HUMAN-PLACE INTERACTION - Tural, Ayşegül; Tural, Ayşegül (My University, 2021)
Neşet Ertaş is one of the important values that represent Anatolian culture and tradition of abdal. There are many works of artistwhose folk songs appeal to Turkish people from past to present. In this research, it is aimed to reveal the geographical elements inNeşet Ertaş folk songs in the context of human-place interaction. During the research process, geographical elements in Neşet Ertaşfolk songs have been collected through document analysis, while folk songs have been used as documents. In this context,qualitative research method has been used in the research. The data obtained from Neşet Ertaş folk songs have been analyzed withhelp of descriptive analysis. According to results of analysis during research process, it has been observed that geographical elementsin Neşet Ertaş folk songs mostly concentrated in the categories of Place, solar system, earth, Earth shapes and Regionalmobility; it is seen that at least it concentrated in the 'Political structure' and 'Artistic-cultural structuring' categories. According toresults of research, it can be said that geographical elements in Neşet Ertaş folk songs, relational data regarding human-place exists,folk songs can create a cultural bond by combining the fields of literature, history, geography in human-place interaction.
Keywords: Folklor; Coğrafya